Inherited Epidermolysis Bullosa: A case report - Mahato, Shyam Kumar; Lama, Susana; Agarwal, Nikhil; Chaudhary, Nagendra (Journal of Universal College of Medical Sciences, 2015)
Epidermolysis bullosa (EB) is a heterogeneous group of genetically determined, mechano-bullous disorders characterized by blister formation in response to mechanical trauma. The blistering of the skin occurs in the varying degrees of severity and can severely incapacitate the life of the afflicted patient. Epidermolysis Bullosa Simplex (EBS), the most commonly occurring type, is dominantly inherited where treatment still remains a major challenge. We report a newborn female with blistering of the skin during the immediate neonatal period.